PENGARUH KEBIJAKAN DEVIDEN, STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PROFATIBITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KEUANGAN DAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Aloysius Gonzaga Danny Rio Yudistira, 16.05.62.0019; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
This research aims to examine and obtain empirical evidence about the effect of dividend policy, capital structure, firm size, and profitability on firm value. The research sample consisted of 42 finance and banking companies that went public on the Stock Exchange.The method was purposive sampling, namely the sampling method by setting certain criteria, finance and banking companies that publish the annual report on period 2014-2017, finance and banking with positive profitability value, so that the pooled data method (2014-2017), obtained the number of observations (n) = 168. Data analysis method uses multiple regression.The results showed that there was no significant and positive effect between dividend policy on firm value, there was a negative and significant influence between capital structure on firm value, there was a positive and significant influence between the firm size on firm value, there was a positive and significant influence between profitability on firm value.